SAT0592 Diurnal Variation of Power Doppler Signal in Metacarpophalangeal Joints of Patients with Rheumatoid Arthritis. (9th June 2015) - Gutierrez, M.; Challal, S.; Ariani, A.; Minichiello, E.; Boissier, M.-C.; Grassi, W.; Semerano, L.
Abstract : Background: In a preliminary study on 10 patients with active rheumatoid arthritis (RA) we could show for the first time that Power Doppler ultrasonography (PDUS) signal of metacarpophalangeal (MCP) joints has a clear diurnal variation, being higher in the morning vs. early afternoon and evening 1 . We undertook a larger study on 50 patients with active RA in order to confirm our preliminary results. Objectives: To test whether PDUS signal of MCP joints in RA patients varies according to the time of day. Methods: A total of 500 MCP joints from 50 patients with active RA (DAS28>3, 2) were evaluated at three different times during the same day T0: between 7 and 10 a.m.; T1: 4-6 hours after T0; T2: 4-6 hours after T1. All joint were evaluated for both presence/absence of PDUS signal and according to a semiquantitative score (from 0 to 3). The results at T0, T1 and T2 were compared for each joint. The day of PDUS assessment, factors that could potentially influence PDUS signal were avoided (smoke, alcohol, corticosteroids, NSAIDs, and vasoactive drugs intake). Room temperature was kept stable. For PDUS examination patients put their hands inside a silhouette drawn on the paper sheet lying on the bench to avoid any change in hands' position across the three examinations. Semiquantitive PDUS scores were compared across the three measures of the day with Friedman's test. Categorical data (PDUS presence/absence) were compared with Cochran's Q test. Results: Globally, 43 out of 50 patients displayed circadian variation of PDUS signal. There was a significant variation in the number of PDUS-positive MCP joints during the day (p<0.05), with more PDUS positive MCP joints at T0 (156) vs. T1 (144) and T2 (129). Semiquantitative PDUS scores were significantly higher at T0 (mean rank 2.18) with a subsequent reduction at T1 (mean rank 1.93) (p<0, 05) and at T2 (mean rank 1.88) (p<0, 05). This pattern of variation (from higher at T0 to lower at T1 and/or T2) was found globally in 88/500 joints, while only in 10 joints PD signal increased during the day. Additionally, in 20 joints the signal was the highest in the morning (T0) and in the evening (T2), with a transitory decrease in the late morning-early afternoon. To note, the different patterns of variation coexisted in the same patient. No significant differences in patterns of PDUS variations were found in patients with high (DAS28>5.1) vs. those with moderate (3.2< DAS28<5.1) disease activity. Conclusions: Diurnal variation of PDUS signal of MCP joints is a frequent finding in patients with active RA, irrespective of the grade of disease activity. PDUS signal in MCP joints is most frequently higher in the morning compared to afternoon and evening. References: Semerano L, Gutierrez M, Falgarone G, et al. Diurnal variation of power Doppler in metacarpophalangeal joints of patients with rheumatoid arthritis: a preliminary study. Ann Rheum Dis. 2011;70:1699-700. Disclosure of Interest: None declared